2007
DOI: 10.1159/000112635
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Activation and Red Blood Cell Phosphatidylserine Exposure Evaluated by Flow Cytometry in Patients with Behçet’s Disease: Are They Related to Thrombotic Events?

Abstract: Behçet’s disease (BD) is associated with an increased risk of venous and arterial thromboses that are associated with morbidity and mortality increase, although the mechanisms are not well established. In the present study, we used whole blood cytometry to determine the exposure of CD62 on the surface of platelets and the expression of phosphatidylserine (PS) on the surface of circulating red blood cells. Microparticle and microaggregate formation from platelets were also determined in a well-classified group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 55 publications
(31 reference statements)
0
12
2
Order By: Relevance
“…However, we did not find any differences in PTS between the patients and the controls. Although higher platelet activation and response to stimulus have been reported in BD patients [13,32], our research group recently published a study of platelet function in the same group of BD patients included in the present study and found no differences in platelet activation markers between the controls and the BD patients, either at baseline conditions or after stimulation with agonists (TRAP and ADP) [33]. After considering this finding and the lack of differences in PTS and platelet contribution to the ROTEM trace between the groups, we conclude that platelets are not the cause of the deviation in the ROTEM results.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not find any differences in PTS between the patients and the controls. Although higher platelet activation and response to stimulus have been reported in BD patients [13,32], our research group recently published a study of platelet function in the same group of BD patients included in the present study and found no differences in platelet activation markers between the controls and the BD patients, either at baseline conditions or after stimulation with agonists (TRAP and ADP) [33]. After considering this finding and the lack of differences in PTS and platelet contribution to the ROTEM trace between the groups, we conclude that platelets are not the cause of the deviation in the ROTEM results.…”
Section: Discussionmentioning
confidence: 99%
“…Quantities of plasma MP are known to be increased in BS, but previous studies these have not addressed an association between MP and thrombosis3435. We investigated the hypothesis that numbers of plasma MP expressing TF are increased in BS.…”
mentioning
confidence: 99%
“…Another study reported increased plasma P‐selectin levels in clinically active BD patients with thrombosis compared to the group of nonthrombotic patients . Platelet hyper‐reactivity may also contribute to the prothrombotic state in BD, with a higher percentage of circulating CD62‐positive platelets and a higher number of circulating microaggregates in patients with a history of thrombosis …”
Section: Discussionmentioning
confidence: 99%